Pengaruh Literasi Keuangan dan Gaya Hidup Terhadap Perilaku Keuangan Mahasiswa - Asdiana, Asdiana; Paleni, Herman; Nasruddin, Nasruddin (Graha Mitra Edukasi, 2024)
This study aims to determine and analyze the effect of financial literacy and lifestyle on the financial behavior of students of management study program at Bina Insan University. This research used 90 respondents as a sample. Research data obtained from the results of direct observation, questionnaires, and documentation. The data analysis technique is PLS (Partial Least Square) test, namely the Measuarent Model/Outer Model, Structural Model/Inner Model, and Hypothesis Test. The results described that the financial literacy and also lifestyle variable had a positive and significant effect on the financial behavior of management study program students at Bina Insan University.